Pengaruh Kualitas Produk, Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian Konsumen di Toko Griyo Camilan Sri Sumingan - Lutfiah Tri Anggraini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Product quality, price, and service are important aspects that greatly influence consumer purchasing decisions, especially in the highly competitive snack retail sector. This study aims to analyze in depth the influence of product quality, price, and service quality on consumer purchasing decisions at the Griyo Snack Shop Sri Sumingan. This study uses a quantitative approach with a survey method. The data collection technique was carried out by distributing questionnaires with a Likert scale to 175 respondents selected using the accidental sampling method, namely sampling based on anyone who accidentally met the researcher and qualified as a consumer. The data obtained were then analyzed using multiple linear regression analysis with the help of SPSS version 23 software. The results of the t-test showed that the variables of product quality, price, and service quality each had a significant influence on consumer purchasing decisions, evidenced by a significance value of 0.000 (less than 0.05). Meanwhile, the F test showed that simultaneously the three variables also had a significant influence on purchasing decisions, with an F-value of 308.162 and a p-value of 0.000. The coefficient of determination (R²) of 0.844 indicates that 84.4% of the variability in consumer purchasing decisions can be explained by product quality, price, and service quality, while the remaining 15.6% is influenced by other factors outside the research variables. This finding implies that business actors in the snack retail sector must pay attention to and improve their product quality, set competitive prices, and provide optimal service to maintain and increase consumer loyalty.